2012
DOI: 10.1080/02755947.2012.680005
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Scale for Cisco Recruitment Dynamics in Lake Superior during 1978–2007

Abstract: The cisco Coregonus artedi was once the most abundant fish species in the Great Lakes, but currently cisco populations are greatly reduced and management agencies are attempting to restore the species throughout the basin. To increase understanding of the spatial scale at which density‐independent and density‐dependent factors influence cisco recruitment dynamics in the Great Lakes, we used a Ricker stock–recruitment model to identify and quantify the appropriate spatial scale for modeling age‐1 cisco recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 55 publications
7
31
1
Order By: Relevance
“…For example, scale of effect for population synchrony of small-bodied Everglades (Florida, USA) fishes occurs at relatively small scales (~10 km), while populations of larger species in the same system synchronise at much larger scales (Chick, Ruetz, & Trexler, 2004;Trexler et al, 2002). Other studies have identified spatial correlation at tens (Bret et al, 2015;Myers, Mertz, & Bridson, 1997) to hundreds of kilometres (Grenouillet et al, 2001;Rook, Hansen, & Gorman, 2012;Tedesco, B., Paugy, D., & Fermon, Y., 2004). This suggest a species-specific (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…For example, scale of effect for population synchrony of small-bodied Everglades (Florida, USA) fishes occurs at relatively small scales (~10 km), while populations of larger species in the same system synchronise at much larger scales (Chick, Ruetz, & Trexler, 2004;Trexler et al, 2002). Other studies have identified spatial correlation at tens (Bret et al, 2015;Myers, Mertz, & Bridson, 1997) to hundreds of kilometres (Grenouillet et al, 2001;Rook, Hansen, & Gorman, 2012;Tedesco, B., Paugy, D., & Fermon, Y., 2004). This suggest a species-specific (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…The effect of correlated climatic conditions on recruitment synchrony (i.e., via the Moran effect; Moran ) has been largely studied in spatially distinct populations, such as the Cisco Coregonus artedi (Rook et al. ; Myers et al. ), Yellow Perch Perca flavescens (Dembkowski et al.…”
mentioning
confidence: 99%
“…However, more recent examples suggest that synchronous recruitment of some lentic fishes can exceed 50 km (Rook et al. ; Myers et al. ).…”
mentioning
confidence: 99%
See 2 more Smart Citations